1м-6дм=. 1м-2дм7см.=. 4м-1м8дм=. 28дм+72дм=. 64дм8см-53дм6см=. 3дм2см-1дм9см=. 63м:9=.

1м-6дм=. 1м-2дм7см.=. 4м-1м8дм=. 28дм+72дм=. 64дм8см-53дм6см=. 3дм2см-1дм9см=. 63м:9=.
Гость
Ответ(ы) на вопрос:
Гость
пиши  только  ответ 1)4  дм 2)8дм  3 см 3)2м  2дм 4)100дм или 1м 5)1дм 3см 6) 7м
Гость
1м - 6дм = 4дм    ;   1м -2дм 7 см= 7 дм 3 см ;   4м - 1м 8дм = 2м 2 дм 28дм + 72 дм = 10 м ;   64дм 8см - 53 дм 6см = 1м 1дм 2 см ;   3дм 2см - 1дм 9см = 1дм 3см ;   63м / 9 = 7м 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы